Legal Pluralism in Environmental Management: Evidence from Bali, Indonesia - Aldyan, Arsyad; Aldyan, Rizal Akbar; Asmanda, Kartika Asmanda Putri; Alasttal, Abdelrahman Alasttal (Ius et Ambientis, 2025)
This study explores the practice of legal pluralism in environmental governance through an in-depth analysis of customary law integration in Bali, Indonesia. As a province that maintains strong Indigenous legal traditions, Bali presents a unique setting where